Effect of Telenursing-Based Health Education on Quality of Life among Patients with Pulmonary Tuberculosis: A Quasi-Experimental Study: Tuberculosis - Achmad Wahdi; Dewi Retno Puspitosari; Erik Irham Lutfi; Endang Mei Yunalia (Institut Kesehatan YARSI Mataram, 2026)
The long duration of pulmonary tuberculosis treatment and the need to take medication regularly can cause treatment fatigue and emotional distress. Limited access to information and emotional support may further affect patients’ quality of life. This study examined whether telenursing-based health education could improve the quality of life of patients with tuberculosis at Jemursari Islamic Hospital, Surabaya. A quasi-experimental pretest–posttest study with a control group was conducted among 38 patients with pulmonary tuberculosis. Participants were randomly divided into an intervention group and a control group. The intervention group received health education through telenursing for four weeks, while the control group received routine care according to hospital standards. Quality of life was measured using a questionnaire. The data were analyzed using paired and independent t-tests, with a significance level of 0.05. Quality of life improved significantly in the intervention group after four weeks of telenursing-based health education (p < 0.001). No significant improvement was observed in the control group. A significant difference was also found between the intervention and control groups after the intervention (p < 0.001). These findings suggest that telenursing-based health education can improve the quality of life of patients with pulmonary tuberculosis. Telenursing may therefore be a useful approach for providing continuous education and support to patients undergoing long-term treatment. This study used a quasi-experimental pre-post-test control group design. The population consisted of 38 tuberculosis patients at Jemursari Islamic Hospital, Surabaya. A sample size of 38 patients, divided into two groups, was selected using random sampling. Data were collected using a questionnaire. Data were analyzed using a t-test with α = 0.05. The paired t-test results showed a P-value of 0.000, indicating a difference in quality of life before and after the telenursing-based health education intervention. In the control group, there was no difference in quality of life before and after the intervention, according to hospital standards. The results of the independent t-test for the intervention and control groups showed a P=0.000, indicating that telenursing-based health education significantly improved quality of life. Telenursing-based health education can improve quality of life. Hospitals and nurses can utilize telenursing to provide health education to patients with chronic diseases.